TANGGUNG JAWAB PT. MANDEVILLA TERHADAP KERUGIAN PEMBELIAN RUMAH DI PERUMAHAN PESONA HARAPAN INDAH KOTA PEKANBARU - Wira Tri Ananda Manalu; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The current position of housing consumers is weak compared to developers as business actors, oftendevelopers commit fraudulent practices to increase their business profits, from the incompatibility of brochureswith housing conditions, low quality of buildings, unavailability of adequate facilities and infrastructure, to lackof housing maintenance. which causes repeated flooding. This happened to the Perumahan Pesona HarapanIndah in Pekanbaru , the housing located on Cengkeh Street, Bukit Raya District experienced repeated floodingevery rainy season. Whereas in Law No. 1 of 2011 concerning Housing and Settlement Areas it is stated that itis forbidden for housing operators to build housing in locations that have the potential to pose a danger to people,thus creating an obligation for PT. Mandevilla as the Developer to provide compensation as stipulated in Article19 of Law No. 8 of 1999 concerning Consumer Protection. The purpose of writing this thesis, namely: First, toknow the responsibilities of PT. Mandevilla as a business actor for the loss of buying a house at PerumahanPesona Harapan Indah Pekanbaru, Second, knows the form of compensation for PT. Mandevilla for the loss ofconsumers of beautiful housing in Pekanbaru.This type of research can be classified in the type of Sociological research because in this study the authordirectly conducts research at the location or place under study in order to provide a complete and clear pictureof the problem being studied. This research is sourced from primary data, secondary data and tertiary data, whilethe population and sample are consumers who buy houses at Perumahan Pesona Harapan Indah and PT.Mandevilla as housing developers.The results of this study indicate, First, the application of the provisions for the acceleration of settlementof The results showed that there are 2 problems that can be concluded. First, the selection of flood-pronelocations and the unavailability of adequate facilities, facilities and infrastructure are factors that determine thatthe Perumahan Pesona Harapan Indah is a product with hidden defects, this results in the loss of security andcomfort for residents of housing in consuming the house as a product, so that PT. Mandevilla is obliged to carryout accountability by providing compensation and/or compensation as stipulated in Article 1365 of the CivilCode and Article 19 of Law No. 8 of 1999 concerning Consumer Protection. Second, PT. Mandevilla has notprovided compensation and/or compensation for the production error of the Perumahan Pesona Harapan Indahas its responsibility as a business actor for causing material and immaterial losses to housing residents. Author'sSuggestion, PT. Mandevilla should provide compensation and/or compensation as a liability for losses that befellthe residents of housing. Second, it is better if a clause for guaranteeing the condition of the house is included inthe sale and purchase agreement so that consumers have a strong basis in demanding accountability.Keywords : Developer – Unlawful Acts – Compensation